Analysis Of Conceptual Understanding Of Aviation Security (AVSEC) Topic Course With Science, Technology, Engineering, And Mathematics (STEM) Approach: Study Of The Perimeter Intrusion Detection System (PIDS) Using Arduino And Pir Sensor - Ahmad Musadek; Bambang Bagus Harianto; Maulana Anifa Silvia; Faoyan Agus Furyanto; Didi Hariyanto; Lady Silk Moonlight (Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze students' conceptual understanding of the "Aviation Security" (AVSEC) course, focusing on the topic of Perimeter Intruder Detection System (PIDS) using the Science, Technology, Engineering, and Mathematics (STEM) approach. This study uses a quasi-experimental design with pre-test and post-test approaches to evaluate the effectiveness of STEM approaches in improving students' conceptual understanding. A total of 25 cadets from the MTU study program, Surabaya Aviation Polytechnic, became the subject of the research. The instruments used include conceptual comprehension tests, observation sheets, questionnaires, and in-depth interviews. The results of data analysis using the Paired Sample T-Test showed that there was a significant increase in student understanding after the application of STEM methods. The average value of the difference between the pre-test and the post-test was -17.750 with a standard deviation of 4.665, and a significance level of 0.000, indicating a significant increase in understanding. The 95% confidence interval for the mean difference is between -19,720 to -15,780. The PIDS system was developed using the Research and Development (R&D) method, while the development of hardware and software followed the Waterfall approach. The results of this research make an important contribution to the development of STEM-based learning methods in the field of aviation safety, especially on the topic of PIDS.